2015
DOI: 10.1179/1476830515y.0000000025
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of fermented soybean products (Cheonggukjang) manufactured by mixed culture ofBacillus subtilisMC31 andLactobacillus sakei383 on trimethyltin-induced cognitive defects mice

Abstract: These results demonstrate that CGK fermented by mixed culture of B. subtilis and L. sakei could exert a wide range of beneficial activities for neurodegenerative diseases, including Alzheimer, Parkinson, and Huntington disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…Here, we sought to study the beneficial effects of melatonin on TMT‐induced neurotoxicity. Trimethyltin chloride induces seizure symptoms and the impairment of learning and memory according to the passive avoidance test, as previously reported . The results of our present study also demonstrated that TMT neurotoxicity is characterized by the deterioration of recognition memory, as shown by the NOR test in mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we sought to study the beneficial effects of melatonin on TMT‐induced neurotoxicity. Trimethyltin chloride induces seizure symptoms and the impairment of learning and memory according to the passive avoidance test, as previously reported . The results of our present study also demonstrated that TMT neurotoxicity is characterized by the deterioration of recognition memory, as shown by the NOR test in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Mental confusion, memory defects, and seizures have been demonstrated to be typical clinical symptoms of acute exposure to TMT . Similarly, acute TMT toxicity induces seizures and deficiencies in learning and memory in rodent models . TMT selectively induces neuronal loss, particularly in the hippocampus .…”
Section: Introductionmentioning
confidence: 99%
“…Expression of nerve growth factor (NGF) and activation of the NGF receptor signaling pathway were also upregulated in the cheonggukjang -treated group. Additionally, the level of SOD activity was enhanced, whereas malondialdehyde was lower in the cheonggukjang -treated group compared to the vehicle-treated group (29). In another study with AD and type 2 diabetes-induced rats, 8-week administration of cheonggukjang extract improved cognitive function and glucose regulation (30).…”
Section: The Effects Of Fermented Foods On Cognitive Functionmentioning
confidence: 97%
“…Cheonggukjang is one of the fermented soybean pastes used in Korean regional cuisine. In an animal study using cheonggukjang extract, a trimethyltin-treated group showed long- and short-term memory loss, whereas groups pretreated with cheonggukjang showed improved memory function in a dose-dependent manner (29). The number of cell death and AChE activity of the hippocampus were decreased in the cheonggukjang -treated group.…”
Section: The Effects Of Fermented Foods On Cognitive Functionmentioning
confidence: 99%
“…Earlier reports (Ademiluyi et al., , ) that characterized the polyphenolic contents of both FLC and FSY via HPLC‐DAD reported the abundance of gallic acid, caffeic acid, quercetin, naringin, and kaempferol in both samples. Copious research findings have reported the bioactive properties of polyphenols and polyphenol‐rich plant extracts to include arginase (Girard‐Thernier et al., ; Oboh et al., ); PDE‐5 (Oboh, Ademiluyi, et al., ; Rahimi et al., ); AChE (Ademiluyi et al., ; Go et al., ; Mathew & Subramanian, ) and ecto‐5′nucleosidase (Akinyemi et al., ; Leal et al., ; Oboh, Adewuni, Ademosun, & Olasehinde, ) modulatory effects. Therefore, the observed enzyme modulatory effects of the condiments extract in this study could be associated with their abundance polyphenolic contents as previously reported.…”
Section: Discussionmentioning
confidence: 99%